2017
DOI: 10.12944/cwe.12.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Trend Analysis of Rainfall in Amaravathi River Basin using Mann-Kendall Test

Abstract: The present study aims to detect the trends in annual and seasonal rainfall and its magnitude in Amaravathi basin, Tamil Nadu. In this study, the mean annual and seasonal rainfall in 10 rain gauge stations of Amaravathi basin have been analysed to determine the trend and its magnitude for the period of 1982-2014. The trend analysis is done using Mann-Kendall and Sen’s slope estimator. The trend analysis results showed wide variations during all the seasons. The increasing trend of rainfall is found to be domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…Cannarozzo et al [34] reported that overall trends in Sicily (Italy) have a negative trend for the entire region by analysing around 250 rain gauges using nonparametric statistical methods. Similar studies for the precipitation (rainfall) trend analysis were carried out over many other regions of the world: Ceballos et al [35] and De Luis et al [36] for Spain; Bunting et al [37] and Hess et al [38] for African countries; Longobardi and Villani [39] and Philandras et al [40] for the Mediterranean area; Ahmad et al [41], Deshmukh and Lunge [42], Kumar et al [43], and Sridhar and Raviraj [44] for the Indian subcontinent; Gemmer et al [45] and Zhai et al [46] for China; Nicholls and Lavery [47] and Salinger and Griffiths [48] for Oceania and de la Casa; and Nasello [49] and Knowles et al [50] for the American continent.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Cannarozzo et al [34] reported that overall trends in Sicily (Italy) have a negative trend for the entire region by analysing around 250 rain gauges using nonparametric statistical methods. Similar studies for the precipitation (rainfall) trend analysis were carried out over many other regions of the world: Ceballos et al [35] and De Luis et al [36] for Spain; Bunting et al [37] and Hess et al [38] for African countries; Longobardi and Villani [39] and Philandras et al [40] for the Mediterranean area; Ahmad et al [41], Deshmukh and Lunge [42], Kumar et al [43], and Sridhar and Raviraj [44] for the Indian subcontinent; Gemmer et al [45] and Zhai et al [46] for China; Nicholls and Lavery [47] and Salinger and Griffiths [48] for Oceania and de la Casa; and Nasello [49] and Knowles et al [50] for the American continent.…”
Section: Introductionmentioning
confidence: 71%
“…e magnitude of the trend at a given time can be found from Sen's slope estimator [72]. e test is widely used in assessing the trend magnitude for rainfall series over the time [41,43,70]; Mondal et al, 2012 [44]. Slope for all data pairs can be calculated by…”
Section: Sen's Slope Estimator Testmentioning
confidence: 99%
“…This test is commonly known as Mann-Kendall test and, as stated above, widely used to check temporal monotonic upward and downward trends of climate (Robson et al 1998;De Luís et al 2000;Cannarozzo et al 2006;Kumar et al 2006;Longobardi and Villani 2009;Ahmad et al 2015;Machina and Sharma 2017;Sridhar and Raviraj 2017). Equation (1) gives the Mann-Kendall statistic S.…”
Section: Mann-kendall Testmentioning
confidence: 99%
“…Sen's slope is used to assess the magnitude of trend at a given time (Sen 1968) and used widely in rainfall trend analysis (Kumar et al 2006;Ahmad et al 2015;Sridhar and Raviraj 2017). Equation (5) is used to calculate slope for all data pairs.…”
Section: Sen's Slope Estimator Testmentioning
confidence: 99%
“…To determine the range of the possible trends in the WUI and ECI indicators and their statistical significance during the 2005 to 2015 period, the nonparametric Sen's slope method and Mann-Kendall test were used. Sen's slope was used to verify the range of the possible trends in the statistical sequence [47,48], and the Mann-Kendall test was selected to substantiate the statistical significance [49,50].…”
Section: Temporal Analysismentioning
confidence: 99%